Development Of Web-Based Information System For Promotion Of Kasongan Craft - Rosa Rusinta (Sean Institute, 2022)
. The development of a Web-Based Information System for the Promotion of Kasongan Pottery Handicrafts serves as a promotional medium for a number of Kasongan pottery company owners who want to promote their handicraft products through the internet. This website provides facilities for web visitors who want to know information about Kasongan pottery, both the products produced and the company that produces the pottery, news about Kasongan, links to Klik_BCA for foreign currency exchange rates, and polls for opinion polls. Information about products includes product photos, descriptions, sizes, colors and prices, so that web visitors can see and know the products produced by a company clearly. Company owners can register as a member of this web online. The facilities provided for members of this web are company product updates, edit company data and change passwords. Members may have their own website outside this website or not have a website at all. This website is built using the Xampp application software package which includes Apache as a web browser, MySQL for databases and PHP as a programming language. For web display design using Macromedia Dreamweaver 8, while for photo editing using Adobe Photoshop CS2 and ACDSee 8. MySQL for database and PHP as programming language. For web display design using Macromedia Dreamweaver 8, while for photo editing using Adobe Photoshop CS2 and ACDSee 8. MySQL for database and PHP as programming language. For web display design using Macromedia Dreamweaver 8, while for photo editing using Adobe Photoshop CS2 and ACDSee 8.